Application Fuzzy AHP-TOPSİS Hybrid Method in Facility Location Selection for Software Systems - Aliyeva, Kamala Rafig (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2024)
Facility location is an integral part of the strategic planning process of almost every organization. Selecting the right location for software systems facilities involves considering various factors to ensure optimal performance, reliability, and cost-effectiveness. For business success, and competitive advantage there are some critical factors that very highly affect facility location. They are proximity to customers, infrastructure, labor quality, total cost, suppliers, etc. The criteria for selecting a facility location may be vaguely defined or open to interpretation. External factors such as economic conditions, political stability, and environmental risks may introduce vagueness and unpredictability into facility location decisions. These factors are often beyond the control of decision-makers but can have significant implications for the success of software systems. In this paper we apply fuzzy AHP-TOPSIS hybrid method for facility location in software systems. This offered model combines the fuzzy AHP and the fuzzy TOPSIS methods. Fuzzy AHP (Analytic Hierarchy Process) and fuzzy TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) are both decision-making methods commonly used in facility location selection. AHP helps in structuring a decision problem into a hierarchy of criteria and alternatives, while TOPSIS ranks alternatives based on their distance to the ideal solution. In the first part of the facility location selection process, we use fuzzy AHP method for determining weights of criteria that are important in selection process. Then by using fuzzy TOPSIS we rank alternatives and select appropriate location for facility.